Social developments in the European Union 2002. Fourth annual report - Degryse, Christophe; Pochet, Philippe (Brussels, 2003)
Social policy issues and, hence, the definition of a European socio-economic model have been at the heart of political debate ever since the Lisbon summit (2000). Tension is unavoidable: a power struggle between different political models, trends and options is underway 'behind the scenes' in Europe. Discussion revolves around content, of course: what form of employment policy can be pursued jointly, how should the issue of pensions be resolved, what approach should be taken to healthcare or public services, and how can employment and economic policy be better integrated?